The Last Graduate (Perpustakaan Tun Abdul Razak, 2023)
The first thing that we want to do is thank God for assisting us in completing the e- magazine that was given to us by our lecturer, MS. Suriani binti Jack, on time. We are very grateful to God for her assistance in this matter. Our team would like to extend its gratitude to MS. Suriani binti Jack, who acted as our lecturer, for his guidance and the information that he shared with us all during the course of the learning process for this magazine. It would be difficult for us to do this e-magazine in the allotted time and get it right if we did not have his instruction. It was a pleasure to acquire new knowledge, but what was much more meaningful were the skills that she was able to instill in us as a result of her unique approach to instructing.